Towards tetanus elimination - Hamdy Ibrahim; Samy Zaky; Mahmoud Hagag; Ahmed S. El Bahawashy; Mohamed Elsawy (The Egyptian Journal of Internal Medicine)
Abstract Tetanus is a serious toxin-mediated disease caused by Clostridium tetani, and it was well-known to ancient physicians and in Greece. The disease is still prevalent in developing countries including Egypt with high morbidity and mortality. It is preventable with a safe and cost-effective vaccine and effective immunization programs. Based on the remarkable success of the World Health Organization (WHO) in reducing maternal and neonatal tetanus throughout the world, lowering tetanus among adults is also possible if a plan for disease elimination is promoted.